Penterjemahan atau penerjemahan: satu analisis korpus data berkomputer - Jumingan, Muhammad Fauzi (Universiti Putra Malaysia Press, 2006)
The lexical of "penterjemahan" and "penerjemahan" have been used by the translators in most of their works. Semantically, both of the particular lexical or words have the same meaning. But morphologically, is it the structure of both lexical still remain or either one must be deleted? There is an opinion that the lexical are borrowed from Arabic words and the alphabet of "T" must be dropped. At the same time, there is also another opinion about the lexical become the Malay word. Therefore, the "T" must be dropped. So, which is the correct one? According to this matter, this article aims to analyse the using of both lexical based on the corpus data that has been developed by the Dewan Bahasa dan Pustaka (DBP) in co-operation with Universiti Sains Malaysia (USM) since years ago. In the context of modern linguistics development, the use of linguistic corpus whether in manual form or computerised, is valid and consider as one of the real and original data or linguistic sample which can be used.